Spatial effects of environmental factors on foreign direct investment: evidence from Chinese cities - Su, Ruiqian (Frontiers in Environmental Science, 2025)
China’s rapid economic growth and the influx of foreign investment have greatly contributed to increased pollutant emissions. As a result, the country faces growing challenges in balancing environmental protection with green economic development. It is crucial to understand the spatial variation in foreign direct investment (FDI) and environmental pollution across cities, as well as the impact of pollution during periods of severe environmental degradation. This study analyzes the spatial distribution and changes over time of FDI and environmental pollution in Chinese cities from 2010 to 2019. It also explores the spatial effects of environmental pollution on FDI. Using a generalized differences-in-differences (DID) model, the research examines how China’s Atmospheric Key Control Zone (AKCZ) policy has affected FDI in cities and their neighboring areas. The results show that cities with higher pollution levels attract less FDI, and pollution in one city can deter investment in surrounding areas. On the other hand, better air quality in a city tends to encourage FDI in nearby regions. The AKCZ policy has a positive impact on FDI within the designated cities but causes a “siphoning” effect in neighboring areas. Well-designed environmental policies are essential for aligning environmental protection with the attraction of foreign investment, ultimately supporting the sustainable development of urban economies.